Handbook of natural resource and energy economics - Kneese, Allen V.; Sweeney, James L. (Amsterdam ; New York : North-Holland ; New York, N.Y., U.S.A. : Sole distributors for the U.S.A. and Canada, Elsevier Science Pub. Co., 1985)
The three volumes comprising the Handbook of Natural Resource and Energy Economics examine the current theory, and sample current application methods for natural resource and energy economics. Volumes 1 & 2 deal with the economics of environmental and renewable resources, and are divided into six parts. The first deals with basic concepts, and subsequent sections are concerned with ethics and environmental topics. Volume 3 deals primarily with non-renewable resources. It analyzes the economics of energy and minerals and includes chapters on the economics of environmental policy.
Volume 1.
Includes bibliographical references and index.
rpm 21/06/2017
Loans
Keywords: Energy industries; Natural resources; Conservation of natural resources; Power resources; Environmental protection; Natural resources $1 (BManagement $1 (BEconomic aspects.s